2021
DOI: 10.1186/s13059-021-02357-4
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous retroviruses in the origins and treatment of cancer

Abstract: Endogenous retroviruses (ERVs) are emerging as promising therapeutic targets in cancer. As remnants of ancient retroviral infections, ERV-derived regulatory elements coordinate expression from gene networks, including those underpinning embryogenesis and immune cell function. ERV activation can promote an interferon response, a phenomenon termed viral mimicry. Although ERV expression is associated with cancer, and provisionally with autoimmune and neurodegenerative diseases, ERV-mediated inflammation is being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 195 publications
(259 reference statements)
0
86
0
Order By: Relevance
“…It should be noted that there are caveats to using mouse models to study ERVs as tumor antigens. While infectious copies of recombined ERVs are common in mice (44,(52)(53)(54)(55)77), human ERVs (HERVs) so far appear to be inactive (42), which could alter the kinetics of antigen expression. Nevertheless, HERVs have long been studied in association with cancer (78)(79)(80)(81).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that there are caveats to using mouse models to study ERVs as tumor antigens. While infectious copies of recombined ERVs are common in mice (44,(52)(53)(54)(55)77), human ERVs (HERVs) so far appear to be inactive (42), which could alter the kinetics of antigen expression. Nevertheless, HERVs have long been studied in association with cancer (78)(79)(80)(81).…”
Section: Discussionmentioning
confidence: 99%
“…TE‐derived cis‐ regulatory sequences also enable p53 to have chromatin pioneering activity that allows p53 to initiate novel gene expression programmes (Sammons et al , 2015 ; Yu & Buck, 2019 ). This could include antiviral and tumour‐suppressive activities or oncogenic and anti‐inflammatory activities or the generation of neo‐antigens (Levine et al , 2016 ; Wylie et al , 2016 ; Buzdin et al , 2017 ; Lemaître et al , 2017 ; Garcia‐Montojo et al , 2018 ; Grandi & Tramontano, 2018 ; Tiwari et al , 2018 ; Xue et al , 2020 ; Jansz & Faulkner, 2021 ).…”
Section: P53 Isoforms Viruses and Other Pathogensmentioning
confidence: 99%
“…Since the studied melanoma cell line was obtained from a metastatic lesion of a nonresponding patient undergoing MAGE-3.A1 T-cell-based peptide immunotherapy, the authors postulated that hypermethylation-induced loss of HLA class I expression may be the cause of the impaired response to vaccination; however, this study highlights for the first time that DNMTis should be tested for their efficiency on reversing the acquired resistance to immunotherapy in CM [ 271 ]. Other preclinical studies have shown that DNMTi may trigger the activation of ERVs, which are normally transcriptionally silenced, leading to the activation of a type I IFN response and cytotoxic T cell recruitment into the TME [ 196 , 272 ]. DNMTi treatments were also linked with CTA induction in melanoma cells, with important pharmacological applications in CM management, as the homogeneous expression of a therapeutic target in neoplastic cells is a prerequisite to effectively target tumors by vaccination-induced CTA-directed immune response [ 273 ].…”
Section: Epigenetics-based Therapies For CMmentioning
confidence: 99%